A Monumental Hellenistic Funerary Ensemble at Callatis on the Western Black Sea The Documaci Tumulus: Volume I - Sîrbu, Valeriu; Ștefan, Maria-Magdalena (Archaeopress Publishing, 2021)
A Monumental Hellenistic Funerary Ensemble at Callatis on the Western Black Sea presents one of the most spectacular early Hellenistic funerary monuments, recently excavated on the western Black Sea coast by a Romanian-Bulgarian-Polish interdisciplinary research team. Documaci Tumulus, covering a painted tomb, and marked by a monumental statue, was built at the threshold of the 4th to 3rd centuries BC in the cemetery of the Greek City of Callatis. The sophisticated construction techniques and the remains of commemorative rituals attest to the dynamic political arena of the Diadochi wars in the Black Sea area and offer a glimpse into a complex and interconnected world of Hellenistic architects and artists. The monument will fuel discussions about the mechanisms of ritualised identity expression in mixed cultural environments, functioning under the pressure of political change, or about community membership, symbolic discourse and ancestors- all reflected in 'le jeu des miroirs' of the funerary practices.